2022
DOI: 10.26641/2307-0404.2022.4.271217
|View full text |Cite
|
Sign up to set email alerts
|

The levels of hypoxia- and angiogenesis-related regulators and matrix metalloproteinase 9 activity in tear fluid of patients with non-penetrating ocular traumas

Abstract: This article was focused on the evaluation of protein biomarkers related to thrombosis, hypoxia, angiogenesis, and tissue remodeling in tear fluid of patients with non-penetrating corneal trauma. 32 patients with non-penetrating corneal injures were enrolled in the study, the control group consisted of 15 healthy patients. Samples of tear fluid were collected from the patients and control volunteers with the use of a disposable end micropipette. Protein levels of D-dimer, hypoxia-inducible factor 1α (HIF-1α), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 8 publications
1
1
0
Order By: Relevance
“…AS are abundantly produced in inflamed and vascularized corneas of experimental animals and play a vital role in regression of excessive neovascularization [11]. Currently, we have found that human tear fluid collected from the eye after non-penetrating corneal injury contains higher concentrations of AS than that of the healthy eye [33]. One of the most intriguing observations made in the present study is the AS-mediated down-regulation of ACE2 in alkali-burned rat cornea.…”
supporting
confidence: 51%
“…AS are abundantly produced in inflamed and vascularized corneas of experimental animals and play a vital role in regression of excessive neovascularization [11]. Currently, we have found that human tear fluid collected from the eye after non-penetrating corneal injury contains higher concentrations of AS than that of the healthy eye [33]. One of the most intriguing observations made in the present study is the AS-mediated down-regulation of ACE2 in alkali-burned rat cornea.…”
supporting
confidence: 51%
“…c-src is known to play a role in bone resorption by regulating osteoclast activity [12]. CtSK is involved in the resorption of calcified cartilage during endochondral bone formation [13], and MMP9 is associated with tissue remodeling, wound healing and angiogenesis [14]. Based on these findings, it might be reasonable to conclude that EA stimulation at the CV4 site can effectively prevent bone loss in the context of breast cancerinduced osteoporosis.…”
Section: Discussionmentioning
confidence: 99%